2003
DOI: 10.1073/pnas.242716099
|View full text |Cite
|
Sign up to set email alerts
|

Expanding expression of the 5-lipoxygenase pathway within the arterial wall during human atherogenesis

Abstract: Oxidation products of low-density lipoproteins have been suggested to promote inflammation during atherogenesis, and reticulocyte-type 15-lipoxygenase has been implicated to mediate this oxidation. In addition, the 5-lipoxygenase cascade leads to formation of leukotrienes, which exhibit strong proinflammatory activities in cardiovascular tissues. Here, we studied both lipoxygenase pathways in human atherosclerosis. The 5-lipoxygenase pathway was abundantly expressed in arterial walls of patients afflicted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
296
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 418 publications
(313 citation statements)
references
References 61 publications
(68 reference statements)
16
296
0
Order By: Relevance
“…Furthermore, 5-LO was localized to macrophages, dendritic cells, foam cells, mast cells and neutrophilic granulocytes, and the number of cells expressing 5-LO was markedly greater in advanced lesions 18 . The leukocytes positive for 5-LO accumulated at distinct sites that are most prone to rupture 29 , such as the shoulder regions below the fibrous cap of the atherosclerotic lesion 18 . A 5-LO promoter variant is associated with abnormal carotid artery intima-media thickness and heightened inflammatory biomarkers 30 .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Furthermore, 5-LO was localized to macrophages, dendritic cells, foam cells, mast cells and neutrophilic granulocytes, and the number of cells expressing 5-LO was markedly greater in advanced lesions 18 . The leukocytes positive for 5-LO accumulated at distinct sites that are most prone to rupture 29 , such as the shoulder regions below the fibrous cap of the atherosclerotic lesion 18 . A 5-LO promoter variant is associated with abnormal carotid artery intima-media thickness and heightened inflammatory biomarkers 30 .…”
Section: Discussionmentioning
confidence: 96%
“…The role of the 5-LO pathway in the pathogenesis of atherosclerosis has recently received attention. A study of postmortem pathologic specimens showed an increase in the expression of members of the 5-LO pathway, including 5-LO and FLAP, in atherosclerotic lesions at various stages of development in the aorta, coronary arteries and carotid arteries 18 . Furthermore, 5-LO was localized to macrophages, dendritic cells, foam cells, mast cells and neutrophilic granulocytes, and the number of cells expressing 5-LO was markedly greater in advanced lesions 18 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations